Negotiated Conversion: Processes in Adaptation, Appropriation, and Contestation in Religious Change - Page, Alexander Gamst (Nova religio, 2026)
Religious conversion is not the rote copying of information from a communicator to a recipient. Rather, it is a complex and multifaceted process located within neophytes and abstracted from and dissipated through their social networks. This paper explores a group of Chinese international students who had converted or were converting to Christianity. Our aim is to show that the conversions observed among the participants revealed a complex set of intertwined processes marked by explicit and tacit discourses where Christian tenets were appropriated, negotiated, adapted, contested, or rejected. The conversions were acts of creation where no two neophytes seemed to espouse exactly the same version of Christianity.